2020
DOI: 10.1371/journal.pbio.3001019
|View full text |Cite
|
Sign up to set email alerts
|

Prediction error signaling explains neuronal mismatch responses in the medial prefrontal cortex

Abstract: The mismatch negativity (MMN) is a key biomarker of automatic deviance detection thought to emerge from 2 cortical sources. First, the auditory cortex (AC) encodes spectral regularities and reports frequency-specific deviances. Then, more abstract representations in the prefrontal cortex (PFC) allow to detect contextual changes of potential behavioral relevance. However, the precise location and time asynchronies between neuronal correlates underlying this frontotemporal network remain unclear and elusive. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 86 publications
(154 reference statements)
5
42
2
Order By: Relevance
“…These studies, as well as our results, suggest that neural responses under anesthesia carry important information that are highly correlated with sensory perception. In the present study, the usage of urethane was chosen to minimize any adverse effect of anesthetics on brain function (Capsius and Leppelsack, 1996;Hara and Harris, 2002;Curto et al, 2009). Furthermore, our findings suggesting distinct neural traces for Ref sequences over the AC in rats under anesthesia are comparable to the findings observed from human neuroimaging study during REM sleep (Andrillon et al, 2017).…”
Section: Discussionsupporting
confidence: 72%
“…These studies, as well as our results, suggest that neural responses under anesthesia carry important information that are highly correlated with sensory perception. In the present study, the usage of urethane was chosen to minimize any adverse effect of anesthetics on brain function (Capsius and Leppelsack, 1996;Hara and Harris, 2002;Curto et al, 2009). Furthermore, our findings suggesting distinct neural traces for Ref sequences over the AC in rats under anesthesia are comparable to the findings observed from human neuroimaging study during REM sleep (Andrillon et al, 2017).…”
Section: Discussionsupporting
confidence: 72%
“…It remains possible that this layer 6 portion of the circuitry plays a different, still uncharacterized role in V1 DD and ensemble membership. Also, it was recently reported that DD appears to increase in magnitude from sub-to primary-to frontal-cortical regions, particularly in the auditory domain (48). One intriguing possibility, which would conform well with predictive coding theories (9), is that the difference from our report lies in the type of neurons recorded; our study selectively recorded PFC neurons which send backward projections to V1 (which convey predictions, not prediction errors), while Casado-Román et al recorded indiscriminately among PFC neurons (48).…”
Section: Discussionmentioning
confidence: 96%
“…In higher order auditory thalamus (medial and dorsal subdivisions), suppression of repeated sounds coexists with enhancement to rare, surprising sounds in single neurons, the so-called stimulus-specific adaptation (SSA; Figure 2 ; Ulanovsky et al, 2003 ) or neuronal mismatch (Parras et al, 2017 ). This property is not restricted to the thalamus but is distributed hierarchically from as early as the auditory midbrain to the auditory cortex and prefrontal cortex (some classical studies: AC, Ulanovsky et al, 2003 ; inferior colliculus, Pérez-González et al, 2005 ; TRN, Yu et al, 2009 ; MGB, Antunes et al, 2010 ; prefrontal cortex, Casado-Román et al, 2020 ). Classically, SSA is elicited using an oddball paradigm, where two tones that differ in their probability of appearance in a sequence are played (a repeated sound interrupted randomly by a deviant sound; Figure 2 ).…”
Section: Role Of Corticothalamic Pathways In the Implementation Of Predictive Processing Frameworkmentioning
confidence: 99%
“…As we progress along the auditory hierarchy, responses to the repeated sound are suppressed, but responses to the deviant are enhanced. Responses to the deviant are maximal in prefrontal cortex (Casado-Román et al, 2020 ). Because their enhanced responses to surprising sounds cannot be explained solely by bottom-up mechanisms of neural fatigue, these neurons are believed to signal expectancy deviance that can be regarded as a prediction error signal (Parras et al, 2017 ; Malmierca et al, 2019 ; Hamm et al, 2021 ).…”
Section: Role Of Corticothalamic Pathways In the Implementation Of Predictive Processing Frameworkmentioning
confidence: 99%
See 1 more Smart Citation